Perspectives on the social order : readings in sociology - Ross, H. Laurence (New York : McGraw-Hill book company, 1963)
The nature of sociology -- The natural conditions of human society -- The geographic factor -- The biological factor -- The demographic factor -- Culture -- The acquisition of culture -- Social organization -- Statuses -- Social differentiation -- Women and men -- City, country, and suburb -- Class and caste -- Color and creed -- Society and its institutions -- Social change.
General
Keywords: Sociología; Cambio social; Cultura